2012
DOI: 10.5455/vetworld.2012.110-117
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Sheep Rumen Fermentation Pattern After Adding Different Levels of Eugenol – Fumaric acid Combinations

Abstract: In vitro gas production technique was used to evaluate the effect of three different levels of eugenol + fumaric acid combinations on rumen fermentation. Rumen contents were collected from five rams immediately after slaughtering and used for preparation of inoculums of mixed rumen microbes that were used in generation of five mass generated and VFAs utilization. In conclusion, the authors recommend using 200 mg L eugenol + fumaric acid combination as an alternative for antibiotic feed additives to optimize ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In the current study, the decrease of the acetate-to-propionate ratio and ammonia nitrogen concentration were also observed in the rumen of the three EOC-or EOAC-added sheep, despite the addition of fumarate in the control sheep. These results are consistent with that of Baraka and Abdl-Rahman (2012), who reported that combined addition of eugenol and fumarate is efficient in reducing methanogenesis and ammonia nitrogen. Fumarate, which serves as a key intermediate in ruminal microbial metabolism, can also decrease the acetate-to-propionate ratio (Ungerfeld et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the decrease of the acetate-to-propionate ratio and ammonia nitrogen concentration were also observed in the rumen of the three EOC-or EOAC-added sheep, despite the addition of fumarate in the control sheep. These results are consistent with that of Baraka and Abdl-Rahman (2012), who reported that combined addition of eugenol and fumarate is efficient in reducing methanogenesis and ammonia nitrogen. Fumarate, which serves as a key intermediate in ruminal microbial metabolism, can also decrease the acetate-to-propionate ratio (Ungerfeld et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Fumarate is an electron acceptor in the rumen that can be used as a hydrogen competitor for methanogens to inhibit methane production (Asanuma et al, 1999;Ungerfeld et al, 2007). Many in vitro studies reported that the addition of fumarate coupled with methane inhibitor can lead to a synergistic effect that can inhibit ruminal methane production (Abdl-Rahman et al, 2010;Baraka and Abdl-Rahman, 2012). Addition of fumarate coupled with EO or EO active components decreases methane and ammonia production, compared with addition of only EO active components (Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ionophores on enteric methane production are related to ciliate protozoal populations and ciliate protozoal populations can adapt to the ionophores present in either low-or high-concentrate diets (Guan et al, 2006). Ever since, different researchers are increasingly looking into plant extracts and plant secondary metabolites that generally are recognized as safe for human consumption (Baraka et al, 2012).…”
Section: Rumen Manipulationmentioning
confidence: 99%
“…The author concluded that coupled addition would improve the impact of fumaric acid on rumen fermentation pattern and can be appropriate alternative for antibiotic feed additives in improving ruminants feed efficiency (Abdl-Rahman, 2010). In vitro evaluation of sheep rumen fermentation pattern after adding different levels of Eugenol+Fumaric acid combination revealed a decrease in pH value, ammonia N concentration and methane production while molar proportion of valeric and isovaleric acids increased and 200mg/l eugenol+fumaric acid combination was recommended as an alternative antibiotic feed additives to optimize rumen fermentation pattern (Baraka and Abdi-Rahman, 2012). Narvaez et al (2011) reported that effect of whole hops on ruminal fermentation being diet and dose dependent and may offer a means of decreasing ruminal methane emission without compromising fermentability of feed.…”
Section: Gebrehiwot Tadesse (Mejs)mentioning
confidence: 99%
See 1 more Smart Citation